Pengaruh Polimer Kristal Cair (LCP) Terhadap Morfologi Campuran Pet/Pen - Wiwik Pudjiastuti (Jurnal Kimia dan Kemasan, 1996)
The experiment of morfology and thermal properties of ternary polymer blends containing liquid crystalline polymer (vectra) has been done using differential scanning calorimeter, x ray measurement and scanning electron microscope.In the case of ternary blends, PET/PEN/LCP (vectra), LCP component were not miscible, with both PEN and PET ones and tended to form fibrous structures in the PET/PEN blend.